Effects of Armolipid Plus on small dense LDL particles in a sample of patients affected by familial combined hyperlipidemia. (December 2015) - Gentile, Marco; Calcaterra, Ilenia; Strazzullo, Alfonso; Pagano, Carmen; Pacioni, Delia; Speranza, Enza; Rubba, Paolo; Marotta, Gennaro
Aim: The aim of this study was to test small dense LDL changes with Armolipid Plus treatment in patients with familial combined hyperlipidemia (FCHL).Methods: After 4 weeks, 30 patients with FCHL were included in an 8-week, randomized, double-blind study and were taking, in addition to the standard diet, either placebo or Armolipid Plus.Results: The placebo group showed no statistically significant differences in the studied parameters; instead, in the Armolipid Plus group, statistically significant reduction differences were detected in BMI (p = 0.010), LDL score (p = 0.035) and an increase in mean LDL particle diameter (p = 0.040).Conclusion: The combination of a standard diet with Armolipid Plus is able to reduce LDL score and increase LDL particle diameter in a group of FCHL after 8 weeks of treatment.